c+7-3=1

Simple and best practice solution for c+7-3=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for c+7-3=1 equation:


Simplifying
c + 7 + -3 = 1

Reorder the terms:
7 + -3 + c = 1

Combine like terms: 7 + -3 = 4
4 + c = 1

Solving
4 + c = 1

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + c = 1 + -4

Combine like terms: 4 + -4 = 0
0 + c = 1 + -4
c = 1 + -4

Combine like terms: 1 + -4 = -3
c = -3

Simplifying
c = -3

See similar equations:

| 2+4n-4n=7-5n | | 2a-3+5a-10a+8= | | 3x-2=7+6 | | 13*7=4x*x | | 805=7h | | 4x+2= | | 9x-6x+x=1 | | 9.5w=76 | | 18=-5b-17 | | 25=125x | | 9y+2x=12 | | 25d=350 | | 27-(-5b)=18 | | 18=2(f-3) | | 2+3y+7+9y= | | x-1.34=-11.8 | | 12-3c=c | | -8x+4=4+8x | | 75=15x | | 6x+2=-22 | | 2y=6x-10 | | 8x-48=9x+27 | | 2.5k=17.5 | | 1.3n-0.03=-9 | | 30x-(5x+4)-11=25x-15x+22(x-1) | | 21x-42=21 | | 3m(2m+9)=0 | | 29n+14-17n=62 | | 16-5k=-k-6k | | 3x+6=-6 | | .75(2x+5)=6 | | 7y+y=-56 |

Equations solver categories